Analysis of Factors Affecting The Variance in Employee Expenditures at The Main Secretariat of The Central Statistics Agency for The 2022-2024 Fiscal Year - Manurung, Debora Patresia Br; Pradana, Mochammad Nugraha Reza (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze the causes of variance in employee expenditure realization at the Main Secretariat of the Central Statistics Agency during the 2022-2024 fiscal year. Variance in employee expenditure is an indicator that describes the accuracy of planning and the effectiveness of budget implementation, so it needs to be studied specifically considering the dominant portion of employee expenditure in the financial structure of BPS. This study uses a descriptive qualitative approach by combining the analysis of Budget Realization Report (LRA) documents, DIPA, as well as interviews with employee expenditure administration management officers (PPABP) and budget analysts. The results of this study show that the variance in the realization of employee expenditure is influenced by several factors, namely changes in the number and composition of employees due to promotions, mutations, and the acceptance of new civil servants and PPPK, changes in the position structure due to PermenPANRB Number 7 of 2022 concerning Work Systems in Government Agencies for Bureaucratic Simplification, THR and Salary 13 payment policies, and changes in tax rules through the TER Income Tax 21 scheme which separates tax allowance accounts from accounts performance allowance. The variance that emerges is positive, indicating the realization that has not yet reached the full budget allocation. These findings underscore the need for more accurate planning, the completion of staffing policies with budgeting, and the strengthening of financial administration.